Tomato plant defense induced by methyl jasmonate impacts on foraging behavior and parasitism of Trichogramma pretiosum. Issue 3 (19th January 2023) - Weber, Nelson Cristiano; Sant'Ana, Josué; Redaelli, Luiza Rodrigues; Dawud, Ezequiel Figueiredo
Abstract: Indirect plant defense may be mediated by volatiles released after oviposition and/or herbivory or by exogenous application of plant hormones such as methyl jasmonate (MeJa), signaling host presence to parasitoids. There is still incipient information regarding phytohormone action on crop plant defense, especially among tomato plants ( Solanum lycopersicum L., Solanaceae) and the parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae). We aimed to evaluate T. pretiosum chemotaxis and parasitism in response to eggs and tomato plants exposed to Tuta absoluta (Meyrick) (Lepidoptera: Gelichiidae) oviposition and herbivory, with and without MeJa. We conducted laboratory (olfactometry and parasitism) and semi‐field (parasitism) bioassays with T. pretiosum in response to treatments with MeJa (0.5 mM) applied to tomato plants, and the interaction with its host, on plants with T. absoluta oviposition and herbivory. Methyl jasmonate presence directly on eggs did not affect T. pretiosum chemotaxis and parasitism. However, it did intensify this natural enemy's foraging behavior and parasitism when applied to the plant. Therefore, the use of MeJa in the T. absoluta and T. pretiosum tomato system may be beneficial, increasing parasitoid recognition and parasitism. Strategies aimed at improving biological control combined with environmentally friendly techniques, such as the use of phytohormones, are of utmost importance towards more sustainable agriculture. Abstract : Indirect defense in plants is mediated by volatiles released into the environment, attracting natural enemies. Chemotactic behavior and parasitism were evaluated of Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) on tomato plants induced by methyl jasmonate and Tuta absoluta (Lepidoptera: Gelichiidae) oviposition and herbivory. Methyl jasmonate on the host eggs did not affect chemotaxis and parasitism of the parasitoid. Yet, search behavior and parasitism were increased on plants induced by both methyl jasmonate and oviposition and herbivory of T. absoluta .